FAO fisheries technical paper N.341: Overview of world elasmobranch fisheries - Ramon Bonfil (FAO, 1994)
Twenty six countries have major elasmobranch fisheries on the basis that their present or recent catches of sharks and rays exceed 10,000t/yr. Information on species, gears, patterns, of exploitation, research and management of elasmobranchs is summarized for each of these countries. The general problems in appraising and managing elasmobranch fisheries and the need for conservation are discussed and possible solutions for some of these problems are proposed.